Reallocation of Water Resources in the Arab Region: An Emerging Challenge in Water Governance - Ambalam, Kannan (European Journal of Sustainable Development, 2014)
Water is an integral part of ecosystems. It is essential to earth’s living creatures and central to maintaining the earth’s ecosystems. In most part of the world, both water quantity and quality problems are becoming more acute, since the limited available water resource are being over-utilized and stressed beyond the sustainability point. The contemporary global water crises including inefficient use and lack of equitable distribution are mainly due to the crises of governance. Water governance emerged as a comprehensive framework by replacing all the existing paradigms including integrated water resource management. Though water governance focuses many aspects in ensuring sustainable use of water resources and its equitable distribution, reallocation of water resources may be most appropriate policy option to achieve these objectives. Reallocation systematically addresses the problems of uneven distribution of water resources across the sectors as well as prevents excessive allocation of water to a particular sector. Based on the secondary sources, this paper analyzes the challenges involved in water governance in terms of water reallocation in the Arab countries where the allocation of water for agriculture is reasonable very high. Addressing water scarcity in the Arab region lies mainly in effectively managing the growing demand. Major water governance challenges with respect reallocation of water resources in the Arab region are tariff, metering and billing, which led to the excessive use in an unprecedented manner. Keywords: Arab Region, Global Water Crisis, Reallocation, Water Governance, Water Management, Water Rights